Perilaku Petani dalam Budidaya Sayuran Daun di Desa Sukorambi Kabupaten Jember Jawa Timur - Sulthoni, Nur Rifqi; Subekti, Sri (AGRIFITIA : Journal of Agribusiness Plantation, 2023)
Leafy vegetable plants are one of the commodities that are extensively cultivated due to the increasing demand for vegetables alongside the population growth. Good cultivation practices will result in the high productivity of these leafy vegetables. Behavior is the action or activity of a person that arises from their perception of something. Behavior can be divided into three domains: knowledge, attitude, and skills. The aim of this research is to assess the knowledge, attitude, and skills of farmers in cultivating leafy vegetable plants in Sukorambi Village, Sukorambi District, Jember Regency. This study employs a qualitative with analysis Miles and Huberman. The reseacrh was conducted in Sukorambi Village, Sukorambi District, Jember Regency, during February to April 2023. The leafy vegetables cultivated consist of commodities such as spinach, mustard greens, water spinach, basil, and crown daisy. The research findings indicate that farmers exhibit certain behaviors in the cultivation of leafy vegetable plants. They produce their own seeds through the process of seed breeding. Soil treatment involves the use of organic manure as a base fertilizer. Planting is done through transplanting techniques for crops like mustard greens and basil. The cultivation process includes watering, weeding, fertilizing, pest and disease control, and harvesting by uprooting or cutting, followed by cleaning the harvested produce.